Rethinking the Role of School Education: a Psychological Aspect (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. The article presents the analysis of the improving the qualityof education program, developed in one of the central schools of the cityfrom the point of a psychological aspect. There is made a brief overviewof the current scientific sources about the lack of psychological literacyof the educational recipients and teachers and the inability to put theexisting knowledge into practice. The basic psychological components ofthe program are investigated in this way: the formation of scientific virtue,the organization of personality-oriented training, the creation of a student’sand teacher’s portfolio as a motivator of activity, the construction of anindividual educational trajectory of an educational recipient. Prospectsfor further exploration in the process of cooperation between higher andsecondary schools are outlined.
Keywords: education recipients; improving the quality of education; personality-oriented learning; activity motivation; self-development; self-improvemen